Effects of low fat addition on chicken myofibrillar protein gelation properties. (May 2019) - Zhou, Lei; Yang, Yuling; Wang, Jingyu; Wei, Sumeng; Li, Shanshan
Abstract: This work aims to study the effects of low fat addition (0.05%–0.25%) on chicken myofibrillar protein (MP) gel properties and ultrastructure. The changes in sulfhydryl, surface hydrophobicity and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) of MP solutions and MP gels were also determined. The results demonstrated that 0.20% fat addition increased MP gel hardness and water holding capacity, and the ratio between protein and fat was 15 to 1 at this time. The rheological curves revealed 0.20% fat treatment increased the G′ values during the heating and cooling stage. A dense and uniform network structure was also observed at 0.20% fat treatment. The changes in the main bands of SDS-PAGE indicated that the addition of fat reduced the rate of protein degradation during MP heating. The total sulfhydryl groups of MP gels showed a downward trend with the fat addition, and the surface hydrophobicity reached the maximum at 0.20% fat addition. The fat addition promoted the formation of disulfide bonds between the MP gel, and enhanced the hydrophobic interaction between MP gel molecules, thereby increased the gel properties of MP. Graphical abstract: Image 1 Highlights: High-fat meat products raise health concern of the consumers. An optimum ratio of protein to fat under low fat conditions was obtained. The gel network structure of the sample gel was clearly observed. Fat addition altered the G′ values of myofibrillar protein during cooling stage. Hydrophobic interaction might be the main forces in fat and protein systems.